Incorporating Physical Activity into the Rehabilitation Process after Spinal Cord Injury - Pelletier, Chelsea A. (My University, 2013)
It is well established that physical activity can improve aspects of physical fitness in individuals with spinal cord injury (SCI). Despite reports of declining health and fitness post-discharge from rehabilitation, there is a limited amount of research exploring exercise status or interventions during this period. The purpose of this dissertation was to investigate the integration of structured exercise into the rehabilitation process following SCI, and to optimize the exercise prescription in the community setting. Findings from the first study indicated that exercise is well tolerated among individuals with sub-acute SCI; performance of a peak exercise test on an arm ergometer was feasible for all injury types. At this stage post-injury, interventions should be mindful of the greater risk of orthostatic intolerance in individuals with complete tetraplegia and focus on building task specific self-efficacy. The second study involved a direct referral and physical activity counselling intervention post-discharge. Adherence rates were excellent among those participants who received the intervention suggesting that this model of care can facilitate adherence to community exercise after discharge.
The final two studies took place in the community. Several modes of adapted exercise were compared and findings indicated that while there were no differences in measures of physiological intensity or enjoyment between the different modes, arm-only exercise was perceived as safer than passive hybrid (arm and leg) exercise. Further, the validity of using ratings of perceived exertion (RPE) to attain prescribed exercise intensity was established. The efficacy of the physical activity guidelines for improving fitness in adults with SCI were evaluated in a community-based randomized controlled trial and the results revealed that the guidelines were effective in improving both aerobic capacity and muscle strength. Taken together, this series of studies describes a model of care that links rehabilitation with community exercise and suggests options for sustained engagement.
Keywords: exercise; spinal cord injury; rehabilitation; health promotion; disability; community; Exercise Physiology; Exercise Science; Health Psychology; Nervous System Diseases; Other Rehabilitation and Therapy; Exercise Physiology